Influence of hypoxia and ischemia preconditioning on bilirubin damage to astrocytes - Falcao, Ana S. (2015)
Hypoxia-ischemia in the perinatal period is a common cause of neurologic disability in children and is often associated with neonatal morbidity and mortality. Another frequent condition of the newborn is hyperbilirubinemia and it is well known that deposi